DEVELOPMENT OF LABOR POTENTIAL OF EMPLOYEES OF PUBLIC ADMINISTRATION BODIES IN MODERN CIRCUMSTANCES - Kirieiev, Ye. (Pressing Problems of Public Administration, 2019)
To analyze the effectiveness of public administration and the activities of public authorities themselves are needed technology and assessment procedures that can be used to timely adjust their performance in terms of achieving social effects based on internal psychological factors. This is possible by creating the conditions for uncovering the work potential of each employee. The purpose of the article is to study the theoretical aspects of the development of the labor potential of employees of public administration authorities in modern circumstances. The labor potential of the employee, organization and society as a whole is a complex system that results from the interaction of the individual with the organizational environment. It can be presented as a set of qualitative and quantitative elements combined by complex interrelations. In the article the structure of components of labor potential of the public administration body according to its types is proposed: physiological, moral-motivational, professional-qualifying, normative-role, adaptation, communicative and leadership. Effective functioning of the system of work potential development of public administration authorities is impossible without quality functioning of the system of labor potential management, which includes the processes of its formation, distribution and use in creating an effective system of planning, control, organization and evaluation of the labor potential of the employee, units and body as a whole, and evaluation of each component of the system of labor potential development and its dynamics. People are both a major factor and an impediment to change. The ability to change is associated with higher levels of education and training, broader specialization, the ability to retrain, the level of creativity and innovation of employees. This suggests that in the future we will have to deal with new models of relationships in labor collectives, which can be conditionally called "staff-process" "staff-social partner".